Complex sporadic colobomata. Issue 6 (June 1978) - Mullaney, J.
Abstract : Sporadic colobomata may be associated with a variety of secondary changes, and these have been classified and discussed with special reference to unusual findings published during recent years. Clinically some cases may appear to be neoplastic, and pathological examination may be important in demonstrating their true nature. A malformation apparently not previously reported is described.